Penerapan Metode Pembelajaran “Bagian” (Teileren Method) Dalam Meningkatkan Hafalan Santri Pondok Pesantren Ilmu Al-Qur’an Hidayatul Qur’an Wonosobo - Diana Faridatul Aulya; Fatkhurrohman Fatkhurrohman; Muhammad Saefullah (Institut Nalanda, 2024)
This thesis aims to: 1) Discover the application of the section (tailored method) in memorization learning for students of Hidayatul Qur'an Hidayatul Qur'an Wonosobo Islamic Boarding School.2) To find out the increase in memorization of Al-Qur'an verses for students after using the section method (tailored method) at Hidayatul Qur'an Islamic Boarding School Wonosobo. This type of research is using qualitative Classroom Action Research (PTK). The subjects of this study were caregivers, administrators, and students of Hidayatul Qur'an Hidayatul Qur'an Wonosobo Islamic Boarding School with a total of 7 students data collection techniques in the process of searching and compiling using observation, test, and interview methods. Then, the data analysis technique used is data collection, data reduction, presenting data, and drawing conclusions and verification. The results of the research are: 1) The implementation of the section learning method (tailored method) to improve the memorization of the Qur'an of Hidayatul Qur'an Hidayatul Qur'an Wonosobo Islamic Boarding School students went well, and in accordance with expectations, student memorization increased. 2) Student learning scores with seven students in pre-cycle learning were 68.09, with a good category. They continued with cycle I, and the percentage of student learning increased to 74.33 with a good category. However, the KKM (Minimum Completeness Criteria) is 75. So, in cycle I, a reflection was held where student memorization had not increased optimally because students were not used to using the section method (tailored method). Therefore, it was necessary to hold cycle II learning. In cycle II, students' learning scores increased very rapidly, namely, increasing to 84.23. This is a reflection that students are accustomed to and have implemented learning using the section method (tailored method).